Kisah-Kisah dalam Kitab Taj al-Salatin dan Siyasatname: Kajian Komparatif - Bastian Zulyeno (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2020)
As a legacy of intellectual works in Malay and Persian literature Taj al-Salatin and Siyasatname are two major works full of wisdom and courtesy reviews. Two books are equally written by the king's closest people and also presented to the King for the sake of achieving a harmonious life between the King and the people. Siyasatname was written by Nizam al Mulk (1018-109 AD) and presented to the king Alp Arselan and Malik Shah (1072-1092 AD) two kings of the Seljuq dynasty, while Taj al-Salatin was written by Bukhari al Jauhari in Aceh (1603 AD) and presented to Sultan Alauddin Riayyat Syah (1589-1603 AD). In the Persian literature the Siyasatname Book got a very important position because this book became a reference for how the King and his aides should manage and manage the kingdom. Likewise with Taj al-Salatin this book reminds the head of government in this case the king and his aides how to become the ideal official figure. This paper will compare the two books of Siyasatname and Taj al-Salatin with structuralist methods. The object of comparison in this paper is only the same story in the two works. Keywords: Taj al-Salatin, Syasatname, Persian, Malay, story. Sebagai peninggalan karya intlektual dalam kesusasteaan Melayu dan Persia Taj al-Salatin dan Siyasatname adalah dua karya besar yang penuh dengan ulasan hikmah dan adab. Dua buku yang sama-sama ditulis oleh orang terdekat raja dan dipersembahkan kepada Raja pula demi tercapainya kehidupan yang harmonis antara Raja dan rakyat. Siyasatname ditulis oleh Nizam al Mulk (1018–109 M.) dan dipersembahkan kepad raja Alp Arselan dan Malik Shah (1072-1092 M.) dua raja dari dinasti Saljuk, sedangkan Taj al-Salatin ditulis oleh Bukhari al Jauhari di Aceh (1603 M) dan dipesembahkan kepada Sultan Alauddin Riayyat Syah (1589-1603 M). Dalam kesusasteraan Persia Kitab Siyasatname mendapat posisi yang sangat penting karena buku ini banyak menjadi rujukan tentang bagaimana seharusnya Raja dan para pembantunya mengurus dan mengelola kerajaan. Begitu juga dengan Taj al-Salatin buku ini mengingatkan kepada kepala pemerintahan dalam hal ini raja dan pembantu-pembantunya bagaimana menjadi sosok pejabat yang ideal. Makalah ini akan membandingkan dua kitab Siyasatname dan Taj al-Salatin dengan metetode strukturalis. Objek perbandingan dalam makalah ini hanya pada kisah yang sama dalam dua karya tersebut. Kata kunci: Taj al-Salatin, Syasatname, Persia, Melayu, cerita.